2014
DOI: 10.1037/h0099843
|View full text |Cite
|
Sign up to set email alerts
|

Parenting and coregulation: Adaptive systems for competence in children experiencing homelessness.

Abstract: The role of effective parenting in promoting child executive functioning and school success was examined among 138 children (age 4 to 6 years) staying in family emergency shelters the summer before kindergarten or first grade. Parent-child coregulation, which refers to relationship processes wherein parents guide and respond to the behavior of their children, was observed during structured interaction tasks and quantified as a dyadic construct using state space grid methodology. Positive coregulation was relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 59 publications
1
36
0
Order By: Relevance
“…In risky or chaotic situations for child rearing, such as poverty or high cumulative adversity, co‐regulation by parents may be particularly important. In a study of families experiencing homelessness, observational coding of effective co‐regulation by parents of young children predicted better school adjustment, apparently mediated by self‐regulation skills in the children that were associated with good parenting (Herbers, Cutuli, Supkoff, Narayan, & Masten, ).…”
Section: Parenting and Parent–child Relationships In Resiliencementioning
confidence: 99%
“…In risky or chaotic situations for child rearing, such as poverty or high cumulative adversity, co‐regulation by parents may be particularly important. In a study of families experiencing homelessness, observational coding of effective co‐regulation by parents of young children predicted better school adjustment, apparently mediated by self‐regulation skills in the children that were associated with good parenting (Herbers, Cutuli, Supkoff, Narayan, & Masten, ).…”
Section: Parenting and Parent–child Relationships In Resiliencementioning
confidence: 99%
“…Second, the types of self-regulatory behaviors that are subsumed within the construct of EF have been linked empirically to success in school for children (e.g., St Clair-Thompson and Gathercole, 2006; Masten et al, 2012; Willoughby et al, 2016) and have recently been the target of interventions to improve academic performance (Diamond and Lee, 2011; Diamond, 2012). Although there are established links between individual differences in EF and academic achievement and adjustment for children, parallel research with the college population is relatively sparse.…”
Section: History Of Child Maltreatment and College Academic Outcomesmentioning
confidence: 99%
“…Additionally, poor parent-child interaction, including child abuse and neglect, during infant and toddler years can adversly impact social and emotional development (Bolger, Patterson, Thompson, & Kupersmidt, 1995;Samuels, Shinn, & Buckner, 2010;Sroufe, 2005). Chronic negative parenting and frequent exposure to traumatic events can lead to behavior issues (i.e., difficulties with impulse control, self-regulation, and sustatined attention) that can negatively impact children's success in school (Herbers, Cutuli, Monn, Narayan, & Masten, 2014;Herbers, Cutuli, Supkoff et al, 2014;Masten, 2012;Narayan, Herbers, Plowman, Gewirtz, & Masten, 2012;Obradovic et al, 2009;Smith, Stagman, Blank, Ong, & McDow, 2011).…”
Section: Families Experiencing Povertymentioning
confidence: 99%
“…It is important to support parents experiencing poverty by teaching positive parenting practices and by offering direct engagement opportunities that promote parentchild bonding (Smith et al, 2011). Parent education groups that teach parents positive control and active listening improve outcomes among their children (Herbers, Cutuli, Supkoff et al, 2014;Yang, 2016). Additionally, there is a growing body of research that has identified mindfulness interventions to improve self-awareness among children and adults with greater self-awareness correlating with improved ability to adapt in adverse situations (Masten, 2015).…”
Section: Families Experiencing Povertymentioning
confidence: 99%
See 1 more Smart Citation